Sexual Dysfunction in Menopausal Women - Dąbrowska-Galas, Magdalena (Sex Med, 2019)
INTRODUCTION: Hormone-related changes in menopause may negatively affect sexual function. AIM: The primary aim of this study was to evaluate sexual functioning in Polish women with the Female Sexual Function Index (FSFI). The secondary aim was to evaluate the major factors affecting sexual functions in middle-aged Polish women. METHODS: The Menopause Rating Scale was used to assess the menopausal symptoms. The Polish translation of the FSFI was used to assess sexual function. OUTCOMES: 69.73% of respondents had sexual dysfunction according to FSFI (FSFI score ≤ 26.55). RESULTS: 80.61% of women experienced menopausal symptoms during the 4-week period of study. Psychological and urogenital symptoms were the most frequently reported among all the women enrolled in the study (78.23% and 77.21%). Sexual problems were observed in women who did not use hormone therapy (β = 0.09, t = −1.97, P = .048) and showed no somatic symptoms (β = 0.03, t = 2.95, P = .002). CLINICAL IMPLICATIONS: It is important for health care providers to ask women about this problem and understand the factors that may influence sexual problems in menopause. STRENGTHS & LIMITATIONS: A validated survey tool was used. The limitation was selection of participants in the clinical setting and sample population size. CONCLUSION: Sexual problems were much more common in women who did not use hormone therapy and showed no somatic symptoms. Dąbrowska-Galas M, Dąbrowska J, Michalski B. Prevalence and Associated Risk Factors of Sexual Problems Among Polish Middle-Aged Women. Sex Med 2019;7:472–479.